John Rawls and Christian social engagement justice as unfairness - Bradley, Anthony B., 1971-; Forster, Greg, 1973-; Arbo, Matthew; Baker, Hunter; Foss, Jerome C.; Kelly, Daniel; Knippenberg, Joseph; McGraw, Bryan; Parks, Matthew; Taliaferro, Karen; Teevan, John Addison; Watson, Micah (Lanham : Lexington Books, 2015)
In this book, leading Christian political thinkers and practitioners critique the Rawlsian concepts of "justice as fairness" and "public reason" from the perspective of Christian political theory and practice. It provides a new level of analysis from Christian perspectives, including implications for such hot topics as the culture war.
Chapter Nine: Rawls and Economic JusticeChapter Ten: Rawls and the Culture War; Conclusion; Bibliography; Index; About the Editors and Contributors.
Print version record.
Keywords: Rawls, John, -- 1921-2002.; Christianity and justice; Christianity and justice; Rawls, John, 1921-2002.; POLITICAL SCIENCE -- Essays; POLITICAL SCIENCE -- Government -- General; POLITICAL SCIENCE -- Government -- National; POLITICAL SCIENCE -- Reference; POLITICAL SCIENCE / Essays; PHILOSOPHY / Political; POLITICAL SCIENCE / Government / General; POLITICAL SCIENCE / Government / National; POLITICAL SCIENCE / Reference; Electronic books